Left ventricular unloading strategies in venoarterial extracorporeal membrane oxygenation patients: how much do we truly understand? - Chung, Jihyuk; Kim, Su Yong; Lee, Juhyun; Cho, Yang Hyun (Acute and critical care, 2025)
KCI Citation Count: 0